2014
DOI: 10.1016/j.otsr.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

AKILE™ total ankle arthroplasty: Clinical and CT scan analysis of periprosthetic cysts

Abstract: IV (retrospective case series).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In past literature, studies have demonstrated the superiority of conventional CT over conventional radiography (CR), suggesting that CR-based studies may not detect PPCs accurately. 1,32,39 Second, publications on cone-beam WBCT in the field of foot and ankle have recently demonstrated the superiority of 3D measurements over traditional two-dimensional (2D) CR-based ones. 17,35 This may suggest that the real alignment of the hindfoot may not be correctly assessed based on the conventional CR-CT sequence, particularly due to perspective distortion, which dramatically influences the value of the measured hindfoot alignment depending on the angle of rotation of the lower limb relative to the radiograph source, 3,5,41 and the absence of weightbearing in the case of conventional CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In past literature, studies have demonstrated the superiority of conventional CT over conventional radiography (CR), suggesting that CR-based studies may not detect PPCs accurately. 1,32,39 Second, publications on cone-beam WBCT in the field of foot and ankle have recently demonstrated the superiority of 3D measurements over traditional two-dimensional (2D) CR-based ones. 17,35 This may suggest that the real alignment of the hindfoot may not be correctly assessed based on the conventional CR-CT sequence, particularly due to perspective distortion, which dramatically influences the value of the measured hindfoot alignment depending on the angle of rotation of the lower limb relative to the radiograph source, 3,5,41 and the absence of weightbearing in the case of conventional CT.…”
Section: Discussionmentioning
confidence: 99%
“…There is wide consensus regarding the higher accuracy of computed tomography (CT) versus conventional radiography (CR) in detecting and quantifying PPCs. 1,32,39 Nevertheless, because of the large amount of radiation, CT scans are usually recommended in the presence of progressive PPCs or suspected implant loosening, but not for regular follow-up. The recently introduced cone-beam weightbearing computed tomography (WBCT), characterized by a low radiation dose, 4 represents a valid and safe diagnostic alternative.…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies have reported that up to 87% of lesions detected on CT scans had initial inaccurate radiographic interpretations. 24,26,33,47,60 We used CT scans to measure cyst size for operative decision making and planning and again at recent follow-up to assess cyst size progression, graft incorporation, and success.…”
Section: Discussionmentioning
confidence: 99%